Poverty and Food Security in Afghanistan : Analysis Based on the National Risk and Vulnerability Assessment of 2007/08 - Islamic Republic of Afghanistan, Ministry of Economy (World Bank, Washington, DC, 2017)
Afghanistan faces a severe problem of poor nutrition and food insecurity. Chronic malnutrition among Afghan children is one of the highest in the world. This report investigates the status of food insecurity in Afghanistan with a focus on mapping provincial differences and an emphasis on understanding the impact of rising food prices on key measures of food security. It synthesizes findings from analysis of rising food prices and their impact on different measures of food access and utilization (such as calorie intake, protein consumption and the quality of diet) in Afghanistan. The findings are based on the analysis of data from the National Risk and Vulnerability Assessment (NRVA) 2007/08, a sample of over 20,000 households from all 34 provinces of Afghanistan. This analytical work is an integral part of the on-going collaboration between the Government of Afghanistan and the World Bank in the domain of poverty and vulnerability assessment. It aims to further the understanding of household wellbeing and vulnerability from the standpoint of food security and complements the earlier work presented in 'poverty status in Afghanistan. Finally, given that poor nutrition and food insecurity affect a sizeable proportion of the Afghan population year-round but more so during bad times, there is genuine need for a scaled-up and well-targeted safety nets program in Afghanistan.